2018
DOI: 10.1108/bij-07-2017-0196
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the drivers for sustainable agri-food waste management

Abstract: Purpose The waste of invaluable agri-food produce is the concern of United Nations Organisation and all countries across the world. The purpose of this paper is to identify and model the drivers of agri-food waste management in India. Design/methodology/approach The interpretive structural modelling method is used to model the drivers in this study. This method helps in understanding the driver-dependent relationships among various drivers/criteria which are selected for studying. Findings The findings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 34 publications
0
36
0
1
Order By: Relevance
“…Thus, as many authors have found in their studies having lack of storage infrastructure give rise to FL (Chauhan et al, 2018;Gogo et al, 2018;Canali et al, 2017;Gogo et al, 2017;Willersinn et al, 2015;Beretta et al, 2013).…”
Section: Production Stage Driversmentioning
confidence: 94%
See 4 more Smart Citations
“…Thus, as many authors have found in their studies having lack of storage infrastructure give rise to FL (Chauhan et al, 2018;Gogo et al, 2018;Canali et al, 2017;Gogo et al, 2017;Willersinn et al, 2015;Beretta et al, 2013).…”
Section: Production Stage Driversmentioning
confidence: 94%
“…Thus far, a few studies have been conducted to determine FL drivers in a different context. Chauhan et al (2018) conducted a study to identify and model the drivers of agri-food waste management in India. Redlingshöfer et al (2017) aimed to measure food loss at the upstream stages of the FSC in industrialized countries.…”
Section: Resource: Compiled By Authorsmentioning
confidence: 99%
See 3 more Smart Citations